Current injection from metal to MoS2 probed at nanoscale by conductive atomic force microscopy. (February 2016) - Giannazzo, F.; Fisichella, G.; Piazza, A.; Di Franco, S.; Oliveri, I.P.; Agnello, S.; Roccaforte, F.
Abstract: Contacts with MoS2 are currently the object of many investigations, since current injection through metal/MoS2 interfaces represents one of the limiting factors to the performance of MoS2 thin film transistors. In this paper, we employed conductive atomic force microscopy (CAFM) to investigate the current injection mechanisms from a nanometric contact (a Pt coated tip) to the surface of MoS2 thin films exfoliated on SiO2 . The analysis of local current–voltage ( I – V ) characteristics on a large array of tip positions provided high spatial resolution information on the lateral homogeneity of the tip/MoS2 Schottky barrier Φ B and of the ideality factor n . From the histograms of the measured Φ B and n values, an average Schottky barrier height of 297 meV with standard deviation of 22 meV and an average ideality factor of 1.65 with a standard deviation is 0.15 have been estimated. The implications of these lateral variations of Φ B and n in MoS2 nano-Schottky diodes on the electrical properties of macroscopic contacts to MoS2 have been discussed also in relation with recent literature results.